2011
DOI: 10.5194/amt-4-843-2011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the application of the optical method to the measurements of the water vapor content in the atmosphere – Part 1: Basic concepts of the measurement technique

Abstract: Abstract. We retrieved the total content of the atmospheric water vapor (or Integrated Water Vapor, IWV) from extensive sets of photometric data obtained since 1995 at Lindenberg Meteorological Observatory with star and sun photometers. Different methods of determination of the empirical parameters that are necessary for the retrieval are discussed. The instruments were independently calibrated using laboratory measurements made at Pulkovo Observatory with the VKM-100 multi-pass vacuum cell. The empirical para… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…As "a" represents the intercept of the T w -PWV fitting line, this result points out the impact of the filter function shape on the PWV retrieval. These results are consistent with those presented in Galkin et al (2011), where a dependence of the "a" parameter on the half-width and shape of the filter function was found. Meanwhile, the parameter "b" can be considered less affected by the transmission curve.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…As "a" represents the intercept of the T w -PWV fitting line, this result points out the impact of the filter function shape on the PWV retrieval. These results are consistent with those presented in Galkin et al (2011), where a dependence of the "a" parameter on the half-width and shape of the filter function was found. Meanwhile, the parameter "b" can be considered less affected by the transmission curve.…”
Section: Resultssupporting
confidence: 82%
“…Furthermore, they showed that a background transmittance ∼ 10 −4 led to an error in aerosol optical depth up to 10 % and significant variations in "a" and "b" parameters in the T w -PWV exponential dependence found by Bruegge et al (1992). Finally, Galkin et al (2011) showed that "a" parameter depends on the half-width and shape of the filter transmission curve, pressure, temperature and water vapor content, while "b" appears only to depend on the latter effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun photometers are widely used for the measurement of the water vapor. The theory of determining content of the vertical atmospheric column PWV by means of a sun photometer is described in detail in Halthore et al (1997), Smirnov et al (2004), Galkin et al (2011) and Barreto et al (2013). Ferrare et al (2006) compare the daytime water vapor measurements of a Raman lidar, sun photometer and radiosonde.…”
Section: Introductionmentioning
confidence: 99%
“…We only focus on accuracy aspects, leaving precision and calibration errors to be addressed in subsequent studies. We also avoid the non-linear complications associated with measurements in the water vapour absorption bands (in the neighbourhood of 940 nm): this subject has already been extensively described in the studies of Galkin and Arkharov (1981), Halthore et al (1997), and Galkin et al (2011Galkin et al ( , 2010.…”
Section: Introductionmentioning
confidence: 99%